Antagonistic and synergistic interactions dominate GHGs fluxes, soil properties and yield responses to biochar and N addition - Jia, Xiaoyu; Yan, Weiming; Ma, Hongze; Shangguan, Zhouping (Frontiers in Environmental Science, 2023)
Applying biochar to soil has been advocated as an effective measure to improve soil fertility and increase carbon (C) sequestration. Biochar is often co-applied with nitrogen (N) fertilizers in agricultural ecosystems, however, the interactive effects of biochar and N addition (BN) on soil greenhouse gases (GHGs) fluxes, soil C and N fractions, and yield has not been investigated. Here, we manipulated a global meta-analysis to explore the effects of biochar and N addition and their interaction on the GHGs, soil C and N fractions, and yield by assembling 75 articles. Results indicate that across all studies, biochar, N, and BN additions all increased soil CO2 emissions (8.5%–29.6%), yield (4.2%–58.2%), soil organic C (SOC, 1.8%–50.4%), dissolved organic C (DOC, 2.7%–30.0%), and total N (TN, 6.8%–15.6%), but had no significant effect on CH4 fluxes. Biochar addition reduced N2O emissions (−21.3%), global warming potential (GWP, −19.8%), greenhouse gas intensity (GHGI, −28.2%), NH4+ (−17.8%) and NO3− (−10.7%), whereas N addition increased these indexes. The interaction effects of BN on CO2 and N2O emissions, GWP, TN, and NH4+ contents were antagonistic, while CH4 emissions, DOC, MBC, NO3−, and yield exhibited synergistic responses. Notably, soil GHGs responses varied depending on geo-climatic factors, edaphic properties, biochar and N treatment parameters, and experimental scenarios. These findings indicate that the co-addition of biochar and N has the potential to mitigate climate change and improve yield, providing a valuable reference for the improvement of climate-smart agriculture.